Development Of Paessler Router Traffic Grapher Network Monitoring Application - Arvianto, Dodik; Kamisutara, Made; Kristiana, Wiwin Agus (IJEEIT : International Journal of Electrical Engineering and Information Technology, 2024)
This study aims to (1) Develop a network monitoring Application as part of the Needs of PT Media Jaya Network Indonesia, (2) Develop a network monitoring Application that has the function of monitoring network traffic, and the condition of existing network devices. This study uses a qualitative research method in the form of development. The primary and secondary data collection in this study was done by PT employees. Media Jaya Network Indonesia, customer data, and network monitoring data at PT. Media Jaya Network Indonesia. The results obtained from this study are (1) Development of network monitoring using the PRTG application can help monitor and manage network performance effectively and efficiently and ensure more optimal service quality to customers. (2) The results of monitoring carried out at PT. Media Jaya Network Indonesia using the PRTG application obtained monitoring data using the Black Box Testing method. Black box testing focuses on testing software functionality so that the application can run properly and identify errors in the system that has been created. The results of the monitoring test are declared valid as a whole, by displaying the dashboard page, displaying up/down devices, displaying network graphs in real-time, and displaying network monitoring results reports.